Corrigendum to "Homogenisation of advective–diffusive transport in poroelastic media" [Mech. Res. Commun. 37 (2010) 133–136]. (April 2016) - Royer, P.; Cherblanc, F.
Abstract: The paper entitled "Homogenisation of advective–diffusive transport in poroelastic media", published in Mechanics Research Communication, Vol. 37, pp. 133–136, contains unfortunately an error in the pore scale description of solute transport. Eq. (11), which expresses the no-mass flux condition over the solid/fluid boundary should include the convection term. This latter does not vanish as a result of solid deformation. This is corrected hereby. A slight modification of the macroscopic coupling term of mechanically induced solute transport is obtained.